Gold Nanoparticles and Their Applications in Engineering - Najah Saud Al-Humairi, Safaa (IntechOpen, 2023)
This book provides a comprehensive overview of gold nanoparticles (AuNPs) and their potential optical, physical, medical, and biological uses. Chapters discuss the synthesis and characterization of AuNPs, clinical applications of AuNPs, the usage of AuNPs as microbial fuel cells, the usefulness of optical exposure to AuNPs, and more.